Benchmarking Subspecialty Practice in Academic Anatomic Pathology - Robert E. Mrak MD, PhD; Tristram G. Parslow MD, PhD; Barbara S. Ducatman MD (Elsevier, 2018)
Assessment of physician workloads has become increasingly important in modern academic physician practice, where it is commonly used to allocate resources among departments, to determine staffing, and to set the compensation of individual physicians. The physician work relative value unit system is a frequently used metric in this regard. However, the application of this system to the practice of pathology has proven problematic. One area of uncertainty is the validity of using work relative value unit norms that were derived from general surgical pathology practice to assess the various subspecialties within anatomic pathology. Here, we used data from the 2017 Association of Pathology Chairs practice survey to assess salary and work relative value unit data for single-subspecialty practitioners in US academic pathology departments in the prior year (2016). Five subspecialties were evaluated: dermatopathology, gastrointestinal pathology, hematopathology/hematology, renal pathology, and neuropathology. Data for general surgical pathologists and cytopathologists were included for comparison. For this analysis, survey data were available for 168 practitioners in 43 US academic departments of pathology. Salary ranges varied little among subspecialties, with the exception of dermatopathology, where salaries were higher. In contrast, work relative value unit productivity varied widely among different subspecialties, with median values differing as much as 4- to 7-fold between subspecialties. These results suggest that the use of a single overall work relative value unit standard is not appropriate for specialty- or subspecialty-based anatomic pathology practice, and that either the benchmark norms should be tailored to individual practice patterns, or an alternative system of workload measurement should be developed.